El crédito de desarrollo humano y la creación de las microempresas en el cantón tena, año 2017. - Zenaida Yolanda, Valiente Cuchipe (2019)
The research project "The Credit for Human Development and the Creation of New Productive Microenterprises in Tena Canton, year 2017", is focused on the analysis of the advantages and disadvantages that have generated human development credits, State policy that was created to finance the establishment and strengthening of productive activities, trade or services of people who belong to the priority attention groups, such as housewives, single mothers, seniors and people with disabilities. In this reason, the principal objective of this research is to determine the incidence of the Human Development Credit in the creation of micro-enterprises in Tena Canton, 2017.It was focused on the families that have been benefited from the CDH in this town. Considering that several social programs, subsidies and monetary transfers have been implemented in the country in order to improve the quality of life of vulnerable groups; Although these aids have not been able to meet the economic needs of multiple families. The research was developed through the logical deduction of primary and secondary sources. It permitted to know the problem, causes, effects which have been generated before, during, and after the execution of this program. For which several methods and techniques were applied (survey, interview, and observation), which permitted a better understanding of the behavior of the variables of the research topic. Finally, the results found in the Human Development Credit research and its impact on the creation of Microenterprises of Tena Canton, will contribute to the decision making of public authorities, students, and society in general.